Students’ English Translation of Islamic Short Stories by The Sixth Semester of English Education Department - Isnawati, Dwi; Toba, Rostanti (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
Translation is one of the best skills that can help us to understand the word, phrase, clause, and sentence in a text or context, to understand the message what the speaker said and especially to communicate each other. This research was conducted based on the research background that is many students got confuse or difficulties to translate sentence. It makes them often fail to understand the meaning of the sentence. The objectives of this research are to know the accuracy, clarity, naturalness, and mechanic of the students’ English translation of Islamic short stories by the sixth semester of English Education Department at IAIN Samarinda in academic year 2019/2020 and to know the quality of the students’ English Translation of Islamic short stories by the sixth semester of English Education Department at IAIN Samarinda in academic year 2019/2020. This research used descriptive quantitative research. The main instrument was the translation text. The subject of the research was the sixth semester students of English Education Department, IAIN Samarinda which consist of 30 students. The collected data were analyzed by using statistic calculation of Mean. The result of this research showed the students’ translating English into Indonesian based on each aspect as follows: first, the result of all the accuracy’s score were 22 (good to average), second, the result of all the clarity’s score was 20 (fair to poor), third, the result of all the naturalness’s score was 16 (very poor), and last, the result of all the mechanic’s score was 12 (very poor). Based on the result of this thesis, that the Mean score is 69,43. The researcher concludes that the class quality in translating English Islamic short stories is the category “Fair” quality.